Study on the thickening behavior and mechanism of supercritical CO2 by modified polysiloxane. (1st September 2022) - Zhao, Mingwei; Yan, Ruoqin; Li, Yang; Wu, Yining; Dai, Caili; Yan, Hui; Liu, Zhiyuan; Cheng, Yunlong; Guo, Xu
Highlights: The solubility and thickening properties of polysiloxane modified by three different functional groups in supercritical CO2 were studied. Vinyl polysiloxane has the best solubility and thickening capacity. The thickening effect of vinyl polysiloxane in supercritical CO2 is affected by its kinematic viscosity and concentration. The higher the kinematic viscosity and concentration of vinyl polysiloxane, the better the thickening ability. Vinyl polysiloxane has the strongest molecular interaction with CO2, and this strong force is electrostatic. Abstract: Supercritical CO2 has been widely concerned because of its clean environmental protection and excellent performance. However, the low viscosity limits its wide application. To this issue, researchers usually use thickeners to improve its viscosity. The siloxane-type polymer is regarded as clean and cheap thickener. In this work, we screened potential supercritical CO2 thickeners by comparing the thickening properties of vinyl polysiloxane, hydroxyl polysiloxane and polydimethylsiloxane. The results show that vinyl polysiloxane has the best thickening performance. The dissolution and thickening behavior of vinyl polysiloxane are further studied. The results indicate that the dissolution pressure and thickening capacity of vinyl polysiloxane in supercritical CO2 increase with the increase of kinematic viscosity and concentration. At the experimental conditions, the maximum viscosity of supercritical CO2 can be increased to 14.87 mPa·s. In addition, the dissolution pressure of vinyl polysiloxane in supercritical CO2 decreases with the increase of cosolvent concentration, while the viscosity slightly decreases. Finally, the thickening mechanism of these thickeners was studied by molecular dynamics simulation. Based on the molecular simulation results, the roles of functional groups of thickeners in the dissolution and thickening process are discussed. It can provide theoretical support for the synthesis and screening of CO2 thickeners in the future.